The potential role of imaging techniques in avoiding neck dissection during salvage surgery after head and neck carcinoma treated with bioradiotherapy. Issue 11 (6th November 2021) - Rovira, A; Tornero, J; Taberna, M; Oliva, M; Montal, R; Nogues, J; Mari, A; Viñals, J M; Lozano, A; Maños, M; Mesia, R
Abstract: Objective: This study aimed to evaluate the effectiveness of computed tomography and positron emission tomography-computed tomography prior to salvage surgery after head and neck carcinoma treated with bioradiotherapy and to look at the role of neck dissection in this setting. Method: This study was a retrospective chart review of a series of consecutive patients with locally advanced head and neck squamous cell carcinoma treated with bioradiotherapy. Radiological and pathological stages were compared to evaluate the accuracy of computed tomography and positron emission tomography-computed tomography in detecting occult neck metastasis in the context of recurrence of primary tumour. In order to assess the impact of neck dissection on survival, Kaplan – Meier survival curves after salvage surgery with and without neck dissection were derived. Results: A total of 268 patients were identified, of which 22 underwent salvage surgery. The negative predictive value of computed tomography and positron emission tomography-computed tomography was excellent. Neck dissection did not represent an improvement on overall, disease specific and regional recurrence free survival ( p = 0.67, p = 0.91 and p = 0.62, respectively) amongst clinically and radiologically negative necks. Conclusion: Conservative treatment of the neck should be considered when dealing with patients with primary site recurrence or persistent disease after bioradiotherapy without evidence of neck disease.